SILURIAN AND DEVONIAN PTERIOMORPH BIVALVES FROM BOLIVIA (Ameghiniana, 2020)
Pteriomorph bivalves from the Silurian and the Devonian beds of Central Andes Basin of Western Gondwana are herein presented. They were collected in ten scattered outcrops in Eastern Cordillera, South of Western Altiplano, South of Interandean and Subandean Bolivia. A total of 54 specimens of a good to regular state of preservation were studied. It is the first time that genera Leptodesma (Leptodesma), Ptychopteria (Ptychopteria) and Ptychopteria (Actinopteria) are reported from Ludlowian beds of the Central Andes Basin: Leptodesma (Leptodesma) sp. B from Corregidores and Huari, Ptychopteria (Ptychopteria) sp. B from Chaquimayu and Ptychopteria (Actinopteria) cf. migrans migrans from Tarabuco and Alarache. A very small Ptychopteria (Actinopteria) sp. is reported from Ludlowian of Tarabuco and from early Lochkovian of Corregidores. It is the first time that Pragian–Emsian pteriomorphs as Ptychopteria (Ptychopteria) sp. A from Sella, and Leptodesma (Leptodesma) sp. A from Huacareta are described. It is also the first time that Eifelian pteriomorphs as Ptychopteria (Actinopteria) eschwegii and Leptodesma (Leptodesma) sp. A from La Escalera and Tiraque-Limbo are documented. This research contributes to the as yet inaccurately known Silurian and Devonian palaeogeography of the Central Andes Basin and is an update of old systematic descriptions of few Pteriomorph bivalves from late 19th and early 20th centuries.